Δ18O and δ2H isotopes, trace metals and major ions in groundwater around uranium and fluoride contaminated Indus valley Quaternary alluvial plain, SW Punjab, India: Implications on hydrogeochemical processes, irrigation use and source. (May 2023) - Chander, Shefali; Paikaray, Susanta; Bansal, Shruti; Sharma, Kritika; Dhiman, Devanshi; Deshpande, R.D.
Abstract: Uranium and fluoride enrichment in groundwater along alluvial plains pose a severe threat to living beings like cancer, fluorosis and crop yield as witnessed around semi-arid southwest Punjab, India. In-situ groundwater was examined for major ions, stable isotopes and trace metals to understand the hydrogeochemical processes, contaminant origin and health risks around SW Punjab, India. Groundwater from a freshly drilled bore well is found to be hard, alkaline, and saline with total dissolved solids and salinity up to 1300 and 1500 mg L −1, respectively. Fluoride (up to 4 mg L −1 ) and uranium (up to 90.07 μg L −1 ) contents exceed permissible limits in most samples and originated from fertilizer inputs and aquifer leaching. Uranium contents decline with depth, while fluoride remains invariable. Decreased U contents are inferred to be caused by U(VI) reduction to U(IV) as evidenced by an increase in Fe 2+ vs. Fe 3+, S 2− vs. S 6+ and N 3− vs. N 5+ with depth. NaHCO3, NaCl + NaHCO3 and NaCl are the dominant water types for shallow (<38 m), intermediate (49–83 m) and deeper groundwater (105–128 m) with Na + and HCO3 − as the dominant cations and anions, respectively. Silicate weathering majorly controlled the groundwater geochemistry together with a partial contribution from cation exchange processes. Unsuitability for drinking and irrigation use is envisaged for all depths, while deeper groundwater is safe in regard to radiological risk. δ 18 O and δD variations are suggestive of evaporation dominance in shallow groundwater, while intermediate groundwater witness canal and groundwater mixing and deeper groundwater are recharged through higher altitude. Graphical abstract: Image 1 Highlights: Alkaline and saline groundwater with high dissolved solids and unsafe for direct use. Na +, HCO3 − and Cl − constitute the dominant ions with NaHCO3 and NaCl water types. Silicate weathering and cation exchange dominantly control hydrogeochemistry. δ 18 O/δD signify evaporation, canal-groundwater mixing and high altitude recharge. Fertilizer inputs and aquifer soil leaching combinedly contribute excess U and F.